CD25 blockade in kidney transplant patients randomized to standard‐dose or high‐dose basiliximab with cyclosporine, or high‐dose basiliximab in a calcineurin inhibitor‐free regimen. (8th October 2015) - Thibault, Gilles; Paintaud, Gilles; Legendre, Christophe; Merville, Pierre; Coulon, Maxime; Chasseuil, Elodie; Ternant, David; Rostaing, Lionel; Durrbach, Antoine; Di Giambattista, Fabienne; Büchler, Matthias; Lebranchu, Yvon
Summary: An increased basiliximab dose may saturate T‐cell CD25 receptors in kidney transplant patients receiving calcineurin inhibitor (CNI)‐free immunosuppression. In a 12‐week study, 16 de novo kidney transplant patients were randomized to (i) 40 mg basiliximab with cyclosporine [ n = 3] (controls), (ii) 80 mg basiliximab with cyclosporine [ n = 6], or (iii) 80 mg basiliximab with everolimus (CNI‐free) [ n = 7], all with mycophenolic acid and steroids. Recruitment was stopped prematurely due to increased biopsy‐proven acute rejection (BPAR) in the basiliximab 80 mg CNI‐free group. BPAR occurred in 1/3, 1/6, and 4/7 patients in the three treatment groups, respectively. The primary endpoint, area under the effect curve of CD25 saturation to week 12, was 8.4(1.6) % × weeks in the control group, 11.1(1.1) % × weeks with basiliximab 80 mg + cyclosporine, and 9.7(0.7) % × weeks in the basiliximab 80 mg CNI‐free group ( P = 0.020 for basiliximab 80 mg + cyclosporine versus controls; P = 0.119 for basiliximab 80 mg CNI‐free versus controls). Although small patient numbers prohibit robust conclusions, these results suggest that doubling the cumulative basiliximab dose to 80 mg does not provide adequate immunosuppression during the first 3 months after kidney transplantation in the absence of CNI therapy (ClinicalTrials.gov number: NCT01596062).